Geographic assessment of the role of agricultural companies in diversifying the sources of income of the Iraqi economy (A Case Study in the district of Mahmudiya) - محمد القيسي, بشار (Al-Adab Journal, 2018)
The privately-owned agricultural companies of the important means in the agricultural sector development and the advancement of its reality, as Iraq has seen in recent years a significant increase in the number of privately-owned agricultural companies scattered in all provinces in the country, as well as profitability targets those companies seeking to achieve class basis, but to have a clear role in the advancement of agricultural reality in quantity and quality, especially after they saw the central and southern provinces are relatively stable in services compared to security in the western provinces of it can be read in this change in the agricultural reality by observing the type of material that are related to the individual consumption of vegetable crops in our daily lives that today it is predominant on the vegetative imported crops, and is therefore an achievement and a paradigm shift in Iraq's agricultural reality in light of the country's dependence on Rent, one of income economic source, but it is oil and that of world prices began to decline causing the economic crisis crippling the countries that adopt it as a source of the sole of their budgets. The study was divided into two main first we dealt with the most important natural factors that have touched the subject of the study directly from the site and the area of ​​soil and water resources in Turn second axis to take up the role of companies in the vertical and horizontal expansion of agricultural production and the most important obstacles facing the work of agricultural companies and concluded the study, a set of conclusions and recommendations.From this point we found it is necessary to highlight the work of those agricultural companies and we took the land the company a model and evaluate its role and achieved notable successes in the development of the agricultural economic base and achieve food security integrated enjoyed by the people and therefore it may be the first step that protect our economy from the need to markets Foreign meet the needs of the domestic market and thus achieves the possibility of getting rid of all forms of dependency.